Combined class I histone deacetylase and mTORC1/C2 inhibition suppresses the initiation and recurrence of oral squamous cell carcinomas by repressing SOX2. (10th July 2019) - Liang, Xueyi; Deng, Miao; Zhang, Chi; Ping, Fan; Wang, Hongfei; Wang, Yun; Fan, Zhaona; Ren, Xianyue; Tao, Xiaoan; Wu, Tong; Xu, Jian; Cheng, Bin; et al.
Abstract: Treatment of oral squamous cell carcinoma (OSCC) remains a challenge because of the lack of effective early treatment strategies and high incidence of relapse. Here, we showed that combined 4SC-202 (a novel selective class I HDAC inhibitor) and INK128 (a selective mTORC1/C2 inhibitor) treatment exhibited synergistic effects on inhibiting cell growth, sphere-forming ability, subcutaneous tumor formation and ALDH1 + cancer stem cells (CSCs) in OSCC. The initiation of OSCC was significantly inhibited by combined treatment in 4NQO-induced rat model. In addition, upregulated SOX2 was associated with advanced and metastatic tumors in OSCC patients and was responsible for the drug-resistance property of OSCC cells. The inhibitory effect of combined treatment on cell viability and ALDH1 + CSCs were attenuated by SOX2 verexpression. Furthermore, combined treatment can effectively overcome chemoresistance and inhibit the growth of recurrent OSCC in vitro and in vivo . Mechanistically, 4SC-202 and INK128 repressed SOX2 expression through miR-429/miR-1181-mediated mRNA degradation and preventing cap-dependent mRNA translation, respectively. These results suggest that combined class I histone deacetylase and mTORC1/C2 inhibition suppresses the carcinogenesis and recurrence of OSCC by repressing SOX2. Graphical abstract: Image 1 Highlights: Combined 4SC-202 (a novel selective class I histone deacetylases inhibitor) and INK128 (a selective mTORC1/C2 inhibitor) treatment exhibits synergistic effects on inhibiting cell growth and reducing ALDH1 + cancer stem cells in OSCC in vitro and in vivo . Combined treatment significantly inhibits the initiation and recurrence of OSCC in rat models induced by 4NQO. 4SC-202 represses SOX2 expression through miR-429/miR-1181-mediated translational repression, while INK128 inhibits SOX2 via preventing cap-dependent mRNA translation.